Methods and models of dose calculation - González, Sara Josefina (International Atomic Energy Agency, 2023)
Fil: González, Sara Josefina. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina